First People, First Voices - Petrone, Penny (Book collections on Project MUSE., 1983)
Speeches, letters, diaries, journals, petitions, prayers, songs, poems, drama and stories covering Indian writing and oratory in Canada from the 1630s to the 1980s. Generally arranged chronologically, also provides the Indian view of Canadian history.